2002
DOI: 10.1002/1522-2624(200208)165:4<397::aid-jpln397>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Plant rhizodeposition — an important source for carbon turnover in soils

Abstract: The soil organic matter plays a key role in ecological soil functions, and has to be considered as an important CO2 sink on a global scale. Apart from crop residues (shoots and roots), left over on the field after harvest, carbon and nitrogen compounds are also released by plant roots into the soil during vegetation, and undergo several transformation processes. Up to now the knowledge about amount, composition, and turnover of these root‐borne compounds is still very limited.  So far it could be demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
207
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(237 citation statements)
references
References 0 publications
7
207
1
6
Order By: Relevance
“…The lower fertility of the Mas d'Imbert soil together with the higher mycorrhization rate of the Myc ϩ genotypes (Table 3) have led to a more significantly beneficial effect of AM symbiosis on plant growth and development in the Mas d'Imbert than in the Châteaurenard soil (Table 2). Since root exudates are influenced quantitatively and qualitatively by the plant growth and development (15,16,17,20), the more significant plant growth promotion by AM in the Mas d'Imbert soil than in the Châteaurenard soil is expected to have impacted more root exudation of the wild type compared to the nonmycorrhizal mutants in the Mas d'Imbert soil than in the Châteaurenard soil. Root exudates are known to influence the genetic structure and diversity of microbial communities in the rhizosphere (18,40), and differences between the bacterial communities associated with mycorrhizal and nonmycorrhizal genotypes in the two soils could then to be related to root exudate variations resulting from the greater promoting effect of AM in the Mas d'Imbert than in the Châteaurenard soil (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The lower fertility of the Mas d'Imbert soil together with the higher mycorrhization rate of the Myc ϩ genotypes (Table 3) have led to a more significantly beneficial effect of AM symbiosis on plant growth and development in the Mas d'Imbert than in the Châteaurenard soil (Table 2). Since root exudates are influenced quantitatively and qualitatively by the plant growth and development (15,16,17,20), the more significant plant growth promotion by AM in the Mas d'Imbert soil than in the Châteaurenard soil is expected to have impacted more root exudation of the wild type compared to the nonmycorrhizal mutants in the Mas d'Imbert soil than in the Châteaurenard soil. Root exudates are known to influence the genetic structure and diversity of microbial communities in the rhizosphere (18,40), and differences between the bacterial communities associated with mycorrhizal and nonmycorrhizal genotypes in the two soils could then to be related to root exudate variations resulting from the greater promoting effect of AM in the Mas d'Imbert than in the Châteaurenard soil (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…To exclude plant genetic influences on the root system and on rhizodeposition the same maize variety as in the field was used. The root biomass and the quantity of C released by living roots depend on the plant phenology and on environmental factors (Grayston et al 1996;Hütsch et al 2002;Nguyen 2003). Plant phenology may influence root biomass as well as rhizodeposition, mainly through root growth dynamics and differences in the quantity of rhizodeposits (Vancura 1964;Klein et al 1988; Van der Krift et al 2001;Jones et al 2004).…”
Section: Factors Affecting Root Biomass And/or Rhizodepositionmentioning
confidence: 99%
“…13 C-and 14 C-isotope labeling studies have revealed the complex dynamics of photoassimilate routing during the growth cycles of cereal crops (see review by Kuzyakov and Domanski 2000). However, most studies used plants at early stages of maturity (less than 60 days after emergence) which may have caused under-or overestimation of C allocation to different soil pools because of changes in plant physiology during the growth cycle (Hütsch et al 2002;Kuzyakov and Schneckenberger 2004;Amos and Walters 2006;Jones et al 2009). For example, root respiration is decreased under mature plants (Kuzyakov 2006), when resources are diverted to reproduction and fruiting (Dungait et al 2011), and the proportion of C translocated belowground and used for root growth, respiration and exudation decreases (Swinnen et al 1994).…”
mentioning
confidence: 99%